KONSEP SEKOLAH RAKYAT DALAM PERSPEKTIF KI HAJAR DEWANTARA - Ahmad Baidowi; Nur Ahyat; Mohammad Fahrudi Noer (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2025)
Abstract This article explores the concept of the People's School based on the views of Ki Hajar Dewantara, a nationalist educational figure who founded Taman Siswa as a form of resistance to the colonial education system. Using qualitative descriptive methods and literature reviews, this study presents several important educational principles, such as the